Pemahaman Hukum Kamma sebagai Landasan Transformasi Moral, Pengendalian Diri, dan Perbaikan Perilaku dalam Pendidikan Budi Pekerti Buddhis - Ani Winarsih (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The law of kamma is a core Buddhist doctrine explaining moral causality grounded in intentional action (cetana). Amid contemporary moral challenges dishonesty, aggression, low self-control, and weakened character education Buddhist moral education requires an internal basis that is both ethically clear and psychologically workable. This article examines how understanding kamma functions as a conceptual foundation for moral transformation, self-regulation, and behavioral improvement in Buddhist character education. Using a qualitative literature review, the study synthesizes canonical teachings and peer‑reviewed research in Buddhist ethics and moral psychology. Findings indicate that a non‑fatalistic understanding of kamma strengthens moral awareness, personal responsibility, reflective judgment, shame and moral dread (hiri–ottappa), and sustained self‑control. Integrating kamma within character education supports disciplined conduct (sīla), mindfulness‑based self‑management, and prosocial behavior that remains stable across contexts.